Dendrimers as anti-inflammatory agents - Pramod K. Avti; Ashok Kakkar (Universidade de São Paulo, 2013)
Dendrimers constitute an intriguing class of macromolecules which find applications in a variety of areas including biology. These hyperbranched macromolecules with tailored backbone and surface groups have been extensively investigated as nanocarriers for gene and drug delivery, by molecular encapsulation or covalent conjugation. Dendrimers have provided an excellent platform to develop multivalent and multifunctional nanoconjugates incorporating a variety of functional groups including drugs which are known to be anti-inflammatory agents. Recently, dendrimers have been shown to possess anti-inflammatory properties themselves. This unexpected and intriguing discovery has provided an additional impetus in designing novel active pharmaceutical agents. In this review, we highlight some of the recent developments in the field of dendrimers as nanoscale anti-inflammatory agents.